EVALUATION OF HYPOLIPIDEMIC ACTIVITY OF FRUIT RIND EXTRACTS OF GARCINIA GUMMIGUTTA IN DIET-INDUCED HYPERLIPIDEMIC RATS - DATCHANAMURTY, BARATHANE; K, MANIMEKALAI; SALWE, KARTIK J (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the hypolipidemic activity of fruit rind extracts of Garcinia gummi-gutta in diet-induced hyperlipidemic rats. Methods: Hydroalcoholic extract of fruit rinds of G. gummi-gutta was prepared using Soxhlet apparatus. 30 Wistar albino rats were divided into five groups (n=6). Except for Group 1, all the other groups were treated with hyperlipidemic diet (HLD) for 4 weeks. After induction, the Groups 3 and 4 were treated with the extracts at 100 mg/kg and 200 mg/kg doses, respectively, whereas Group 5 received the standard drug atorvastatin at 10 mg/kg for the next 4 weeks. Lipid profile was estimated at the end of each week. At the end of the study, rats were sacrificed and the liver and heart were analyzed for histopathological changes. Data expressed as mean±standard error of the mean. Statistical analysis was done using one-way ANOVA followed by post hoc Tukey test. p<0.05 considered statistically significant. Results: The serum levels of total cholesterol (TC), triglycerides (TG), very low-density lipoprotein (VLDL), and LDL were significantly increased and the levels of high-density lipoprotein (HDL) were significantly decreased when compared to normal control. The groups which received G. gummi-gutta rind extract at 100 mg/kg and 200 mg/kg showed a significant decrease in the mean cholesterol, TG, LDL, VLDL levels, and an increase in HDL levels when compared to the HLD group. The group which received the extract at higher dose (REGG200) was found better than the lower dose (REGG 100). REGG 200 showed significant improvement in increasing the HDL levels than all the test groups. The standard drug atorvastatin was found better than REGG100 but there was no significant difference between high doses of the extract and atorvastatin. Conclusion: The fruit rinds extract of G. gummi-gutta was able to decrease the elevated serum lipids (TC, TG, LDL, and VLDL) and consequently increase the HDL levels in a dose-dependent manner.